IADC/SPE Drilling Conference 2006
DOI: 10.2118/99104-ms
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of Drilling Fluids and Cased-Hole Cleaning: What Is Sufficient Cleaning?

Abstract: TX 75083-3836, U.S.A., fax 1.972.952.9435. AbstractThe need for an efficient displacement of drilling fluids from cased wells prior to installation of completion equipment has been relatively undisputed in the past.Several different fluid systems has been applied as well as a variety of different mechanical tools to achieve what is considered to be a clean well in order to safely run advanced completion equipment in the well. In contradiction to the requirements related to running more advanced equipment in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…Berg et al developed a fowchart for ensuring efective displacements for wellbore cleanliness of open holes and cased holes prior to running completion by depending on nephelometric turbidity units (NTUs), which are a measure of the opacity of the fuid used for displacements. Te main indication of fuid cleaning efectiveness during wellbore cleaning displacement is no remaining drilling mud in the top of the upset connections [173]. Njobuenwu and Wobo conducted an experimental study and concluded that the ES of an oil-based drilling fuid decreases as the concentration of modifed bentonite (organophilic clay) increases.…”
Section: Rheology Modeling Factors Indicators Experiments Andmentioning
confidence: 99%
“…Berg et al developed a fowchart for ensuring efective displacements for wellbore cleanliness of open holes and cased holes prior to running completion by depending on nephelometric turbidity units (NTUs), which are a measure of the opacity of the fuid used for displacements. Te main indication of fuid cleaning efectiveness during wellbore cleaning displacement is no remaining drilling mud in the top of the upset connections [173]. Njobuenwu and Wobo conducted an experimental study and concluded that the ES of an oil-based drilling fuid decreases as the concentration of modifed bentonite (organophilic clay) increases.…”
Section: Rheology Modeling Factors Indicators Experiments Andmentioning
confidence: 99%